Chromosomal and morphological taxonomy of larvae of Simulium (Gomphostilbia) (Diptera: Simuliidae) in Thailand - Phasuk, J.; Chanpaisaeng, J.; Adler, P. H.; Courtney, G. W. (Zootaxa, 2005)
The larvae of 12 species of Simulium in the subgenus Gomphostilbia in Thailand, including one species newly recorded from Thailand (Simulium novemarticulatum) and four undescribed species, were analyzed chromosomally. All larvae had a chromosomal complement of n = 3. Positions of landmarks in the IIS arm, specifically the positions of the bulge and the ring of Balbiani, permitted the identification of most species, including some that were morphologically indistinguishable. Species with the IIS landmarks in similar positions differed in larval morphology. The combination of chromosomal landmarks in the IIS arm and selected structural features, especially the form of the cuticular setae on the larval abdomen and the configuration of the postgenal cleft and gill histoblast, permitted accurate identification of all 12 species. The larva and pupa of S. novemarticulatum are characterized for the first time.